Analysis of the use of genomic DNA as a universal reference in two channel DNA microarrays - Gadgil, Mugdha; Lian, W.; Gadgil, Chetan J.; Kapur, V.; Wu, WS (BMC Genomics, 2005)
Background: DNA microarray is an invaluable tool for gene expression explorations. In the two-dye microarray, fluorescence intensities of two samples, each labeled with a different dye, are compared after hybridization. To compare a large number of samples, the 'reference design' is widely used, in which all RNA samples are hybridized to a common reference. Genomic DNA is an attractive candidate for use as a universal reference, especially for bacterial systems with a low percentage of non-coding sequences. However, genomic DNA, comprising of both the sense and anti-sense strands, is unlike the single stranded cDNA usually used in microarray hybridizations. The presence of the antisense strand in the 'reference' leads to reactions between complementary labeled strands in solution and may cause the assay result to deviate from true values. Results: We have developed a mathematical model to predict the validity of using genomic DNA as a reference in the microarray assay. The model predicts that the assay can accurately estimate relative concentrations for a wide range of initial cDNA concentrations. Experimental results of DNA microarray assay using genomic DNA as a reference correlated well to those obtained by a direct hybridization between two cDNA samples. The model predicts that the initial concentrations of labeled genomic DNA strands and immobilized strands, and the hybridization time do not significantly affect the assay performance. At low values of the rate constant for hybridization between immobilized and mobile strands, the assay performance varies with the hybridization time and initial cDNA concentrations. For the case where a microarray with immobilized single strands is used, results from hybridizations using genomic DNA as a reference will correspond to true ratios under all conditions. Conclusion: Simulation using the mathematical model, and the experimental study presented here show the potential utility of microarray assays using genomic DNA as a reference. We conclude that the use of genomic DNA as reference DNA should greatly facilitate comparative transcriptome analysis.

Population proportion approach for ranking differentially expressed genes - Gadgil, Mugdha (BMC Bioinformatics, 2008)
Background: DNA microarrays are used to investigate differences in gene expression between two or more classes of samples. Most currently used approaches compare mean expression levels between classes and are not geared to find genes whose expression is significantly different in only a subset of samples in a class. However, biological variability can lead to situations where key genes are differentially expressed in only a subset of samples. To facilitate the identification of such genes, a new method is reported. Methods: The key difference between the Population Proportion Ranking Method (PPRM) presented here and almost all other methods currently used is in the quantification of variability. PPRM quantifies variability in terms of inter-sample ratios and can be used to calculate the relative merit of differentially expressed genes with a specified difference in expression level between at least some samples in the two classes, which at the same time have lower than a specified variability within each class. Results: PPRM is tested on simulated data and on three publicly available cancer data sets. It is compared to the t test, PPST, COPA, OS, ORT and MOST using the simulated data. Under the conditions tested, it performs as well or better than the other methods tested under low intraclass variability and better than t test, PPST, COPA and OS when a gene is differentially expressed in only a subset of samples. It performs better than ORT and MOST in recognizing non differentially expressed genes with high variability in expression levels across all samples. For biological data, the success of predictor genes identified in appropriately classifying an independent sample is reported.

Comparison of feature selection and classification combinations for cancer classification using microarray data - Vijayan, V.; Bulsara, B.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2009)

Increase in efficiency of media utilization for recombinant protein production in Chinese hamster ovary culture through dilution - Thombre, Shreya; Gadgil, Mugdha (Biotechnology and Applied Biochemistry, 2011)
Animal cells are extensively used for the large-scale production of recombinant proteins. Processes and genetically engineered cell lines have been developed to enhance longevity of the culture and increase protein productivity. In this study, we tested the effect of diluting a culture of Chinese hamster ovary (CHO) cells with phosphate-buffered saline (PBS) on cell growth and efficiency of media utilization. An immunoglobulin G-expressing CHO cell line was cultured in CD CHO media followed by dilution of the culture with PBS after the end of the exponential phase. A 28% and 61% increase in protein yield per milliliter of media was observed in the diluted culture in the batch and fed-batch mode with glucose and protein hydrolysate feeding, respectively. To aid in analyzing the potential causes of this observed increase, an unstructured mathematical model was constructed using previously reported kinetics to simulate cell growth, nutrient utilization, and protein production. The model predicts an increase in recombinant protein yield per milliliter of media in PBS diluted cultures under both batch and fed-batch conditions, and suggests that this observed increase could at least partly be due to a decrease in inhibitor concentration in the diluted culture.
Keywords: chemically defined media; culture dilution; glucose consumption; inhibitor formation; recombinant protein yield

Controlled release of nutrients to mammalian cells cultured in shake flasks - Hegde, Swati; Pant, Tejal; Pradhan, Ketaki; Badiger, Manohar V.; Gadgil, Mugdha (Biotechnology Progress, 2012)
Though cell culture-based protein production processes are rarely carried out under batch mode of operation, cell line and initial process development operations are usually carried out in batch mode due to simplicity of operation in widely used scale down platforms like shake flasks. Nutrient feeding, if performed, is achieved by bolus addition of concentrated feed solution at different intervals, which leads to large transient increases in nutrient concentrations. One negative consequence is increased waste metabolite production. We have developed a hydrogel-based nutrient delivery system for continuous feeding of nutrients in scale down models like shake flasks without the need for manual feed additions or any additional infrastructure. Continuous delivery also enables maintaining nutrient concentrations at low levels, if desired. The authors demonstrate the use of these systems for continuous feeding of glucose and protein hydrolysate to a suspension Chinese Hamster Ovary (CHO) culture in a shake flask. Glucose feeding achieved using the glucose-loaded hydrogel resulted in a 23% higher integral viable cell density and an 89% lower lactate concentration at the end of the culture when compared with a bolus-feed of glucose. (c) 2011 American Institute of Chemical Engineers Biotechnol. Prog., 2012

Effect of addition of `carrier' DNA during transient protein expression in suspension CHO culture - Pradhan, Ketaki; Gadgil, Mugdha (Cytotechnology, 2012)
Transient protein expression using polyethyleneimine as a transfection agent is useful for the rapid production of small amounts of recombinant proteins. It is known that an increase in extracellular DNA concentration during transfection can lead to a nonlinear increase in intracellular DNA concentration. We present an approach that hypothesizes that this nonlinearity can be used to decrease the amount of plasmid required for productive transfections. Through addition of non coding `carrier' DNA to increase total DNA concentration during transfection, we report a statistically significant increase in protein (IgG) expression per unit plasmid used for transfection. This approach could be useful to increase protein yields for large scale transfections under conditions where plasmid availability is limited.
Keywords: Carrier DNA; Cell age; DNA: polyethyleneimine particle size; Medium equilibration with CO2; pH excursion; Salmon sperm DNA; Transient protein expression

In situ pH maintenance for mammalian cell cultures in shake flasks and tissue culture flasks - Pradhan, Ketaki; Pant, Tejal; Gadgil, Mugdha (Biotechnology Progress, 2012)
pH in animal cell cultures decreases due to production of metabolites like lactate. pH control via measurement and base addition is not easily possible in small-scale culture formats like tissue-culture flasks and shake flasks. A hydrogel-based system is reported for in situ pH maintenance without pH measurement in such formats, and is demonstrated to maintain pH between 6.8 and 7.2 for a suspension CHO cell line in CD CHO medium and between 7.3 and 7.5 for adherent A549 cells in DMEM:F12 containing 10% FBS. This system for pH maintenance, along with our previous report of hydrogels for controlled nutrient delivery in shake flasks can allow shake flasks to better mimic bioreactor-based fed batch operation for initial screening during cell line and process development for recombinant protein production in mammalian cells. (C) 2012 American Institute of Chemical Engineers Biotechnol. Prog., 2012
Keywords: high throughput screening; pH control for cell culture; pH control in shake flask; pH control in tissue culture flasks; small scale platforms for cell culture

Regulation of BACE1 by miR-29a/b in a cellular model of spinocerebellar ataxia 17 - Roshan, Reema; Ghosh, Tanay; Gadgil, Mugdha; Pillai, Beena (RNA Biology, 2012)
Polyglutamine diseases are a class of neurodegenerative disorders characterized by expansion of polyglutamine repeats, protein aggregation and neuronal cell death in specific regions of the brain. The expansion of a polyglutamine repeat in the TATA binding protein (TBP) causes a neurodegenerative disease, Spinocerebellar Ataxia 17 (SC A17). This disease is characterized by intranuclear protein aggregates and selective loss of cerebellar neurons, including Purkinje cells. MicroRNAs are small, endogenous, regulatory non-coding RNA molecules that bind to mRNAs with partial complementarity and interfere in their expression. Here, we used a cellular model of SC A17 where we expressed TBP with 16 (normal) or 59 (pathogenic) polyglutamines and found differential expression of several microRNAs. Specifically, we found two microRNAs, miR-29a/b, were downregulated. With miR-29a/b downregulation, we found an increased expression of targets of miR-29a/b-beta-site amyloid precursor protein cleaving enzyme 1 (BACE 1), p53 upregulated modulator of apoptosis (PUMA) and BAK, increased cytochrome c release and apoptosis. Restoration of miR-29a/b in the pathogenic polyglutamine background reduced the BACE 1 expression. While, antagomiRs against miR-29a/b resulted in an increase in BACE 1 levels and neuronal apoptosis. In spite of the elevation of BACE 1 in Alzhemiers disease, its role in neuronal cell death has not been established. Here, we show that increased BACE 1 expression is not sufficient to cause apoptosis. However restoring level of BACE 1 to normal in polyglutamine cells partially reduced neuronal apoptosis. We show a role for the miR-29a/b-BACE 1 regulatory interaction in SC A17, suggesting that this microRNA could be part of a common molecular mechanism leading to neuronal cell death in multiple neurodegenerative disorders. The identification of a common mechanism of microRNA mediated neurodegeneration not only improves our understanding of the process, but also provides promising and novel therapeutic targets.
Keywords: BACE1; miR-29a/b; neurodegeneration; SCA17; TBP

Comparison of methods for identifying periodically varying genes - Vijayan, V.; Deshpande, P.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2013)

In situ pH management for microbial culture in shake flasks and its application to increase plasmid yield - Sanil, Reenu; Maralingannavar, Vishwanathgouda; Gadgil, Mugdha (Journal of Industrial Microbiology & Biotechnology, 2014)
Shake flasks are widely used to culture microorganisms, but they do not allow for pH control without additional infrastructure. In the presence of a carbon source like glucose, culture pH typically decreases due to overflow metabolism and can limit the growth of microorganisms in shake flasks. In this study, we demonstrate the use of magnesium hydroxide-loaded pH managing hydrogels (m-pHmH) for in situ base release to counter the decrease in culture pH in shake flasks using Escherichia coli as a model organism, in both complex and mineral salts medium. Base release from m-pHmH is shown to increase with decreasing pH (22-fold increase in release rate from pH 8 to 5), thus providing feedback from culture pH. The addition of m-pHmH resulted in better pH maintenance and higher biomass yields of E. coli K12 in media containing glucose as a carbon source. The use of m-pHmH with additional buffer resulted in pH being maintained above 6.9 while pH decreases below 5 without m-pHmH. We demonstrate one application of such in situ pH management to increase the volumetric plasmid yield from E. coli in shake flask culture. In situ glucose release through a hydrogel to mimic fed-batch culture along with the addition of m-pHmH resulted in a 395 % increase in volumetric plasmid yield to 38 mu g/ml in shake flask culture.
Keywords: In situ pH control; Magnesium hydroxide; pH-responsive base release; Shake flask culture

Uptake of Azo dyes into silk glands for production of colored silk cocoons using a green feeding approach - Nisal, Anuya; Trivedy, Kanika; Mohammad, Hasan; Panneri, Suyana; Sen Gupta, Sayam; Lele, Ashish K.; Manchala, Ramesh; Kumar, Nirmal S.; Gadgil, Mugdha; Khandelwal, Harish B.; More, Snehal; Laxman, Ryali Seeta (ACS Sustainable Chemistry & Engineering, 2014)
Dyeing of textile fabrics is considered to be one of the most polluting industries today, and there is a need to develop green processes that can reduce this pollution. A promising technology that can potentially cleanup the dyeing of silk fibers that are widely used for textile applications would involve the generation of intrinsically colored silk cocoons. This can be achieved by feeding of Bombyx mori silkworm larvae with a modified feed of mulberry leaves containing a sprayed dye solution. This process significantly reduces the need for treating toxic dye effluents that are generated in traditional dyeing processes. In this report, we have evaluated a set of seven different azo dyes that are used in the textile industry for dyeing to produce intrinsically dyed silk. The dyes used in the study had similar chemical structures with systematically varying partition coefficients. The results suggest that while some dyes produced intrinsically colored silk other did not. Careful evaluation of the physical properties of these related azo dyes suggest that the balance of hydrophobic and hydrophilic character is necessary for diffusion of the dye from the alimentary canal of the silkworm larva into the hemolymph and later into the silk glands. The partition coefficient of the dye also determines the preferential association of the dye with either sericin or fibroin protein in the silkworm gland and finally into the cocoon. These insights are extremely important in development of novel dye molecules that can be successfully fed to Bombyx mori silkworm larvae for producing intrinsically colored silk of various colors and shades.
Keywords: Azo dyes; Biochemical pathways; Color silk; Dye uptake; `' Green `' silk

Cell line development for biomanufacturing processes: recent advances and an outlook - Le, Huong; Vishwanathan, Nandita; Jacob, Nitya M.; Gadgil, Mugdha; Hu, Wei-Shou (Biotechnology Letters, 2015)
At the core of a biomanufacturing process for recombinant proteins is the production cell line. It influences the productivity and product quality. Its characteristics also dictate process development, as the process is optimized to complement the producing cell to achieve the target productivity and quality. Advances in the past decade, from vector design to cell line screening, have greatly expanded our capability to attain producing cell lines with certain desired traits. Increasing availability of genomic and transcriptomic resources for industrially important cell lines coupled with advances in genome editing technology have opened new avenues for cell line development. These developments are poised to help biosimilar manufacturing, which requires targeting pre-defined product quality attributes, e.g., glycoform, to match the innovator's range. This review summarizes recent advances and discusses future possibilities in this area.
Keywords: Biomanufacturing; Biosimilars; Cell line development; CHO cells genomics; Genome editing; Transcriptomics

Development of a mathematical model for animal cell culture without pH control and its application for evaluation of clone screening outcomes in shake flask culture - Gadgil, Mugdha (Journal of Chemical Technology and Biotechnology, 2015)
BACKGROUNDCurrently used mathematical models for animal cell growth and metabolism cannot simulate changing culture pH and its effect on metabolism, and hence cannot accurately model cultures lacking pH control. Animal cell cultures are however widely cultured at a small scale without pH control, e.g. for clone screening during cell line development. A mathematical model for animal cell growth without pH control is developed and applied to design optimal conditions for clone screening without pH control. RESULTSThe mathematical model successfully simulates published data for suspension CHO culture in shake flasks. It is further used to simulate clonal heterogeneity and predict relative clone performance in different culture conditions. Predictions of correlation coefficients between clone titers in batch and fed batch screening conditions and pH controlled fed batch agree with published values. Fed batch mode is predicted to give better screening outcomes than batch, but only for clones able to consume lactate. Simulations reveal that culture duration of the screening assay has a large effect on the screening outcome and optimal durations differ based on the ability or inability of clones to consume lactate. CONCLUSIONThis study presents a tool for optimal design of screening assay for clone selection without pH control. (c) 2014 Society of Chemical Industry
Keywords: clone screening; clone selection; culture duration; high throughput screening; lactate consumption; mathematical model with pH effects; pH control for animal cell culture

Manganese increases high mannose glycoform on monoclonal antibody expressed in cho when glucose is absent or limiting: implications for use of alternate sugars - Surve, Tanaya; Gadgil, Mugdha (Biotechnology Progress, 2015)
Alternate sugars such as galactose and fructose are metabolized at a slower rate than glucose and result in lower accumulation of lactate. While low lactate accumulation is desirable, we report that complete substitution of glucose with these sugars results in an increase in M5 high mannose glycans. Surprisingly, this increase is much higher when the culture is supplemented with manganese: for example, when cells are cultured with galactose, M5 high mannose glycan content increased from 5% at 1 nM Mn2+ in the basal medium to 32% with 16 mu M Mn2+ supplementation. When galactose is supplemented with glucose maintained at low concentrations, a small reduction in high mannose glycans is seen. In control cultures with glucose, the high mannose content was however <2% in this range of Mn2+ concentration. By varying Mn2+ and glucose supplementation levels, with or without galactose, we systematically demonstrate that Mn2+ concentration and glucose availability, together, significantly affect the high mannose glycan content. To our knowledge, this is the first report that shows that the effect of Mn2+ on high mannose glycan content depends on glucose availability. At each Mn2+ supplementation level evaluated, galactosylation percentages were highest for cultures where galactose was supplemented with glucose at non-limiting concentration. (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:460-467, 2015
Keywords: CHO; fructose; galactose; glucose; glycosylation; high-mannose glycan; manganese

Shear stress increases cytotoxicity and reduces transfection efficiency of liposomal gene delivery to CHO-S cells - Rawat, Jyoti; Gadgil, Mugdha (Cytotechnology, 2016)
Animal cells in suspension experience shear stress in different situations such as in vivo due to hemodynamics, or in vitro due to agitation in large-scale bioreactors. Shear stress is known to affect cell physiology, including binding and uptake of extracellular cargo. In adherent cells the effects of exposure to shear stress on particle binding kinetics and uptake have been studied. There are however no reports on the effect of shear stress on extracellular cargo delivery to suspension cells. In this study, we have evaluated the effect of shear stress on transfection of CHO-S cells using Lipofectamine 2000 in a simple flow apparatus. Our results show decreased cell growth and transfection efficiency upon lipoplex assisted transfection of CHO-S while being subjected to shear stress. This effect is not seen to the same extent when cells are exposed to shear stress in absence of the lipoplex complex and subsequently transfected, or if the lipoplex is subjected to shear stress and subsequently used to transfect the cells. It is also not seen to the same extent when cells are exposed to shear stress in presence of liposome alone, suggesting that the observed effect is dependent on interaction of the lipoplex with cells in the presence of shear stress. These results suggest that studies involving liposomal DNA delivery in presence of shear stress such as large scale transient protein expression should account for the effect of shear during lipoplex assisted DNA delivery.

Cell culture processes for biopharmaceutical manufacturing - Gadgil, Mugdha (Current Science, 2017)
Recombinant proteins manufactured using animal cell culture processes comprise a significant fraction of biopharmaceuticals. With the expiry of patents on this class of therapeutics, there is also a significant interest in manufacture of biosimilar versions of such therapeutics. This article provides a birds-eye view of upstream process development for animal cell culture processes, with a focus on advances pertinent to the development of processes for biosimilars.
Keywords: Biopharmaceutical; Cell line development; CHO; glycosylation; monoclonal antibody

CHO Cells Adapted to Inorganic Phosphate Limitation Show Higher Growth and Higher Pyruvate Carboxylase Flux in Phosphate Replete Conditions - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology progress, 2017)
Inorganic phosphate (P-i) is an essential ion involved in diverse cellular processes including metabolism. Changes in cellular metabolism upon long term adaptation to P-i limitation have been reported in E. coli. Given the essential role of P-i, adaptation to P-i limitation may also result in metabolic changes in animal cells. In this study, we have adapted CHO cells producing recombinant IgG to limiting P-i conditions for 75 days. Not surprisingly, adapted cells showed better survival under P-i limitation. Here, we report the finding that such cells also showed better growth characteristics compared to control in batch culture replete with P-i ( higher peak density and integral viable cell density), accompanied by a lower specific oxygen uptake rate and cytochrome oxidase activity towards the end of exponential phase. Surprisingly, the adapted cells grew to a lower peak density under glucose limitation. This suggests long term P-i limitation may lead to selection for an altered metabolism with higher dependence on glucose availability for biomass assimilation compared to control. Steady state U-C-13 glucose labeling experiments suggest that adapted cells have a higher pyruvate carboxylase flux. Consistent with this observation, supplementation with aspartate abolished the peak density difference whereas supplementation with serine did not abolish the difference. This supports the hypothesis that cell growth in the adapted culture might be higher due to a higher pyruvate carboxylase flux. Decreased fitness under carbon limitation and mutations in the sucABCD operon has been previously reported in E. coli upon long term adaptation to P-i limitation, suggestive of a similarity in cellular response among such diverse species. (C) 2017 American Institute of Chemical Engineers

Differential responses of CHO cells adapted to limitation of inorganic phosphate, glucose or glutamine - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Pant, Tejal; Gadgil, Chetan; Panchagnula, Venkateswarlu; Gadgil, Mugdha (255th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nexus of Food, Energy, and Water, 2018)

In situ base release for pH maintenance can allow shake flasks to better mimic bioreactor performance for CHO cell culture - Maralingannavar, Vishwanathgouda; Shenoy, Bharath R.; Hazarika, Jahnabi; Unnikrishnan, Divya; Prabhu, Anuja; Maity, Sunit; Gadgil, Mugdha (Journal of Chemical Technology & Biotechnology, 2018)
BACKGROUNDShake flasks are widely used for evaluating mammalian cells in suspension. Lack of pH control can contribute to differences in culture performance between them and bioreactors. This study evaluates whether a previously reported in situ base releasing hydrogel (pHmH) to counter pH decrease can enable shake flask cultures to better mimic bioreactor cultures. RESULTSCompared with bioreactor culture, fed-batch cultures of a recombinant Chinese hamster ovary (CHO) cell-line in shake flasks without pHmH showed a decrease in pH to 6.6, accompanied by 40, 60 and 22% lower peak cell density, lactate accumulation, and immunoglobulin G (IgG) titer, respectively. Use of pHmH allowed shake flasks to maintain pH above 6.8 and reduced this difference to 20, 30, and 15%, respectively, thus enabling culture performance in shake flasks to better mimic the bioreactor. IgG glycosylation profiles were similar in identically fed cultures across all three platforms. Application of pHmH hydrogel during clone screening was evaluated by comparing correlation between titers for five recombinant CHO clones in bioreactors and shake flasks with and without pHmH; a higher correlation was found in shake flasks with pHmH than without. CONCLUSIONIn situ base release through hydrogel can allow identically fed fed-batch cultures in shake flasks to better mimic cell growth, lactate accumulation and IgG titers in bioreactors, without additional infrastructure. (c) 2018 Society of Chemical Industry.

Zinc supplementation decreases galactosylation of recombinant IgG in CHO cells - Prabhu, Anuja (Applied Microbiology and Biotechnology, 2018)
Trace element composition of culture medium can be altered to modulate glycoform of recombinant glycoproteins. In this study, we show that Zn2+ supplementation at or above 100 μM decreases galactosylation of recombinant IgG expressed in Chinese Hamster Ovary cells. This decrease in galactosylation is not due to reduced galactosyltransferase expression. This effect persists upon supplementation of galactose and uridine to the culture, indicating that it may not be due to reduced UDP-Gal availability. Measurements of galactosyltransferase activity in the cell lysate show that activity decreases with increasing Zn2+/Mn2+ ratio. This suggests that one possible explanation of the effect of Zn2+ may be reduced intracellular galactosyltransferase activity due to increase in Zn2+/Mn2+ ratio. Consistent with this, the decrease in galactosylation of IgG could be reversed by supplementation of Mn2+ (a cofactor of galactosyltransferase) which increases intracellular Mn2+ content. Measurement of total intracellular Zn2+ content, however, indicates no significant upregulation of total intracellular Zn2+ content and no significant downregulation of intracellular Mn2+ content with Zn2+ supplementation. One possible explanation could be that cellular detoxification response to higher extracellular Zn2+ concentration might lead to changes in intracellular distribution of Mn2+. In this case, Zn2+ supplementation would be expected to interfere with other known effects of Mn2+. Indeed, the previously reported increase in high mannose glycans upon Mn2+ supplementation in the absence of glucose is reversed by Zn2+ supplementation. This study also suggests the use of Mn2+ supplementation as a strategy to overcome the effect of lot-to-lot variability in trace element concentrations on galactosylation.
Keywords: CHO cells; glycosylation; manganese; Trace metals; zinc

Superfluous glutamine synthetase activity in Chinese Hamster Ovary cells selected under glutamine limitation is growth limiting in glutamine-replete conditions and can be inhibited by serine - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology Progress, 2019)
Passaging and expansion of animal cells in lean maintenance medium could result in periods of limitation of some nutrients. Over time, such stresses could possibly result in selection of cells with metabolic changes and contribute to heterogeneity. Here, we investigate whether selection of Chinese Hamster Ovary (CHO) cells under glutamine limitation results in changes in growth under glutamine-replete conditions. In glutamine-limiting medium, compared to control cells passaged in glutamine-rich medium, the selected cells showed higher glutamine synthetase (GS) activity and attained a higher peak viable cell density (PVCD). Surprisingly, in glutamine-replete conditions, selected cells still showed a higher GS activity but a lower PVCD. We show that in glutamine-replete medium, PVCD of selected cells was restored on (a) inhibition of GS activity with methionine sulfoximine, (b) supplementation of aspartate-without affecting GS activity, and (c) supplementation of serine, which is reported to inhibit GS in vitro. Consistent with the reported effect of serine, inhibition of GS activity was observed upon serine supplementation along with reduced growth of cells under glutamine-limiting conditions. The latter observation is important for the design of glutamine-free culture medium and feed used for GS-CHO and GS-NS0. In summary, we show that CHO cells selected under glutamine limitation have superfluous GS activity in glutamine-replete medium, which negatively affects their PVCD. This may be due to its effect on availability of aspartate which was the limiting nutrient for the growth of selected cells in glutamine-replete conditions.
Keywords: C-13 tracer analysis; CHO cells; glutamine limitation; Glutamine synthetase; GS-CHO; GS-NS0; selection under nutrient limitation; serine

Towards in situ continuous feeding via controlled release of complete nutrients for fed-batch culture of animal cells - Rawat, Jyoti; Gadgil, Mugdha (Biochemical Engineering Journal, 2020)
Small-scale culture of animal cells in suspension is of importance for many applications. At a small-scale, fed-batch is achieved either by manual bolus feeding or the use of liquid handling robots. In this study, we report an alternate application of a hydrogel for in situ continuous delivery of a nutrient feed comprising 18 amino acids, vitamins, antioxidants, and trace elements. We show that amino acid release is sustained for at least seven days. Importantly, release rates of individual amino acids can be independently modulated by changing their loading. We demonstrate the application of this hydrogel for complete in situ feeding of nutrients to a suspension adapted CHO cell line expressing IgG leading to 2.7-fold and 4-fold improvement in integral viable cell density (IVCD) and volumetric productivity respectively. This is similar to improvements obtained by bolus liquid feeding. Further, supplying glucose from the same hydrogel to eliminate manual feeding led to a 1.8-fold increase in IVCD accompanied by a 3-fold increase in volumetric productivity as compared to batch culture. In summary, this study provides a proof-of-concept that hydrogels can enable completely closed in situ feeding for mammalian cell culture requiring no external intervention. Such continuous in situ delivery can potentially enable closed culture systems maintaining nutrients at low levels mimicking physiological concentrations.
Keywords: Amino acids; CHO cells; Closed system; Fed-batch; Hydrogel for continuous feeding; In situ nutrient release

Trace metals in cellular metabolism and their impact on recombinant protein production - Prabhu, Anuja; Gadgil, Mugdha (Process Biochemistry, 2021)
Replacement of serum and increasing use of chemically defined media demands optimisation of trace metal components for biomanufacturing applications. Trace metal availability can impact culture performance, productivity and product quality. Several trace metals are cofactors of metabolic and other enzymes, and thus their availability regulates cellular metabolism. Additionally, they can also affect the availability of other trace metals and stability of some medium components. Such factors also need to be considered while formulating trace metal concentrations in the culture medium. Due to their very low concentrations, these components are susceptible to substantial variability arising from contaminants from other raw material and leaching from process equipment and can contribute to process variability. Understanding the role and impact of trace metals will help develop strategies to achieve targeted process parameters and increase process robustness vis-`a-vis any lot-to-lot variability in trace metal concentration in culture medium. This review describes the role of trace metals, particularly manganese, copper and zinc, in central carbon metabolism to aid in understanding the basis of metal-mediated effects on culture performance and provides a comprehensive review of the reported impact of trace metals on CHO cell culture performance and recombinant protein quality.
Keywords: Chinese hamster ovary cells; glycosylation; Medium formulation; Process variability; Product quality; Recombinant proteins; Trace metals

Engineering nucleotide sugar synthesis pathways for independent and simultaneous modulation of N-glycan galactosylation and fucosylation in CHO cells - Prabhu, Anuja; Shanmugam, Dhanasekaran; Gadgil, Mugdha (Metabolic Engineering, 2022)
Glycosylation of recombinant therapeutics like monoclonal antibodies (mAbs) is a critical quality attribute. N-glycans in mAbs are known to affect various effector functions, and thereby therapeutic use of such glycoproteins can depend on a particular glycoform profile to achieve desired efficacy. However, there are currently limited options for modulating the glycoform profile, which depend mainly on over-expression or knock-out of glyco-syltransferase enzymes that can introduce or eliminate specific glycans but do not allow predictable glycoform modulation over a range of values. In this study, we demonstrate the ability to predictably modulate the gly-coform profile of recombinant IgG. Using CRISPR/Cas9, we have engineered nucleotide sugar synthesis pathways in CHO cells expressing recombinant IgG for combinatorial modulation of galactosylation and fucosylation. Knocking out the enzymes UDP-galactose 4 `-epimerase (Gale) and GDP-L-fucose synthase (Fx) resulted in ablation of de novo synthesis of UDP-Gal and GDP-Fuc. With Gale knock-out, the array of N-glycans on recom-binantly expressed IgG is narrowed to agalactosylated glycans, mainly A2F glycan (89%). In the Gale and Fx double knock-out cell line, agalactosylated and afucosylated A2 glycan is predominant (88%). In the double knock-out cell line, galactosylation and fucosylation was entirely dependent on the salvage pathway, which allowed for modulation of UDP-Gal and GDP-Fuc synthesis and intracellular nucleotide sugar availability by controlling the availability of extracellular galactose and fucose. We demonstrate that the glycoform profile of recombinant IgG can be modulated from containing predominantly agalactosylated and afucosylated glycans to up to 42% and 96% galactosylation and fucosylation, respectively, by extracellular feeding of sugars in a dose-dependent manner. By simply varying the availability of extracellular galactose and/or fucose, galactosylation and fucosylation levels can be simultaneously and independently modulated. In addition to achieving the pro-duction of tailored glycoforms, this engineered CHO host platform can cater to the rapid synthesis of variably glycoengineered proteins for evaluation of biological activity.
Keywords: Antibody; Cell engineering; Fucosylation; Fx; Galactosylation; Gale; glycosylation; Nucleotide sugar synthesis; Recombinant therapeutics

Mathematical model of the multi-amino acid multi-transporter system predicts uptake flux in CHO cells - Sreejan, Ashley; Gadgil, Mugdha; Gadgil, Chetan J. (Journal of Biotechnology, 2022)
Supply and uptake of amino acids is of great importance to mammalian cell culture processes. Mammalian cells such as Chinese hamster ovary (CHO) cells express several amino acid (AA) transporters including uniporters and exchangers. Each transporter transports multiple AAs, making prediction of the effect of changed medium composition or transporter levels on individual AA transport rate challenging. A general kinetic model for such combinatorial amino acid transport, and a simplified analytical expression for the uptake rate as a function of amino acid concentrations and transporter levels is presented. From this general model, a CHO cell-specific AA transport model, to our knowledge the first such network model for any cell type, is constructed. The model is validated by its prediction of reported uptake flux and dependencies from experiments that were not used in model construction or parameter estimation. The model defines theoretical conditions for synergistic/repressive effect on the uptake rates of other AAs upon external addition of one AA. The ability of the CHO-specific model to predict amino acid interdependencies experimentally observed in other mammalian cell types suggests its robustness. This model will help formulate testable hypotheses of the effect of process changes on AA initial uptake, and serve as the AA transport component of kinetic models for cellular metabolism.
Keywords: Amino acid transport; CHO cell; Exchanger; mathematical model; Multiple transporters

Amino acid abundance and composition in cell culture medium affects trace metal tolerance and cholesterol synthesis - Rawat, Jyoti; Bhambri, Aksheev; Pandey, Ujjiti; Banerjee, Sanchita; Pillai, Beena; Gadgil, Mugdha (Biotechnology Progress, 2023)
Amino acid compositions of cell culture media are empirically designed to enhance cell growth and productivity and vary both across media formulations and over the course of culture due to imbalance in supply and consumption. The interconnected nature of the amino acid transporters and metabolism suggests that changes in amino acid composition can affect cell physiology. In this study, we explore the effect of a step change in amino acid composition from a DMEM: F12-based medium to a formulation varying in relative abundances of all amino acids, evaluated at two amino acid concentrations (lean LAA vs. rich HAA). Cell growth was inhibited in LAA but not HAA. In addition to the expected effects on expression of the cell cycle, amino acid response and mTOR pathway genes in LAA, we observed an unanticipated effect on zinc uptake and efflux genes. This was accompanied by a lower tolerance to zinc supplementation in LAA but not in the other formulations. Histidine was sufficient but not necessary to prevent such zinc toxicity. Additionally, an unanticipated downregulation of genes in the cholesterol synthesis pathway was observed in HAA, accompanied by an increase in cellular cholesterol content, which may depend on the relative abundances of glutamine and other amino acids. This study shows that changes in the amino acid composition without any evident effect on growth may have profound effects on metabolism. Such analyses can help rationalize the designing of medium and feed formulations for bioprocess applications beyond replenishment of consumed components.
Keywords: Amino acids; cell culture medium; CHO cells; Cholesterol; zinc

Leveraging machine learning to dissect role of combinations of amino acids in modulating the effect of zinc on mammalian cell growth - Pandey, Ujjiti; Madhugiri, Indrani; Gadgil, Chetan; Gadgil, Mugdha (BIOTECHNOLOGY PROGRESS, 2024)
Keywords: Absorption; Cytotoxicity; ENTEROCYTES; HISTIDINE